Antiviral effects of phytochemicals against severe acute respiratory syndrome coronavirus 2 and their mechanisms of action: A review. (7th November 2022) - Jantan, Ibrahim; Arshad, Laiba; Septama, Abdi Wira; Haque, Md. Areeful; Mohamed‐Hussein, Zeti‐Azura; Govender, Nisha T.
Abstract: The worldwide spreading of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has posed a serious threat to health, economic, environmental, and social aspects of human lives. Currently, there are no approved treatments that can effectively block the virus although several existing antimalarial and antiviral agents have been repurposed and allowed use during the pandemic under the emergency use authorization (EUA) status. This review gives an updated overview of the antiviral effects of phytochemicals including alkaloids, flavonoids, and terpenoids against the COVID‐19 virus and their mechanisms of action. Search for natural lead molecules against SARS‐CoV‐2 has been focusing on virtual screening and in vitro studies on phytochemicals that have shown great promise against other coronaviruses such as SARS‐CoV. Until now, there is limited data on in vivo investigations to examine the antiviral activity of plants in SARS‐CoV‐2‐infected animal models and the studies were performed using crude extracts. Further experimental and preclinical investigations on the in vivo effects of phytochemicals have to be performed to provide sufficient efficacy and safety data before clinical studies can be performed to develop them into COVID‐19 drugs. Phytochemicals are potential sources of new chemical leads for the development of safe and potent anti‐SARS‐CoV‐2 agents.